The Institution, the Economy and the Market: Karl Polanyi's Institutional Thought for Economists - Maucourant, Jerome; Plociniczak, Sebastien (Review of Political Economy, 2013)
This paper aims to clarify the logical structure of Karl Polanyi's concept of institution, especially with regard to his most important contribution to political economy—the conception of self-regulating markets as institutions. Although Polanyi did not provide a well-developed concept of institution, this article argues that such a concept exists in his work. Moreover, there is in Polanyi's work a sophisticated institutionalist account of the self-regulating market that has been largely overlooked as Polanyi does not present it explicitly. Analyzing the economy as an institutionalized process, as Polanyi does, reveals that the market is neither a natural nor a spontaneous phenomenon—a conclusion that runs counter to conventional economic thinking. Polanyi's approach enables us to view capitalism (the ‘market society’ in Polanyi's language) through a highly specific cultural fact: the fiction of the self-regulating market. This institutional perspective needs to be reassessed beyond new-institutionalist theoretical constructions.
Keywords: economic structure; free enterprise; institutions (philosophy); philosophy of economics; social facts